Iâ€™m From Ngruki, but Donâ€™t Judge Me As A Terrorist: Critical Victimology Study of Muslims Community in Ngruki, Sukoharjo, Indonesia - Ireka, Radhistya; Sulhin, Iqrak (ARISTO, 2023)
The Ngruki area has been in the spotlight after the Bali bombings and several acts of terrorism. Causes there are perpetrators who are caught by police in Ngruki. Also, there is a boarding school led by Abu Bakar Bakar Ba'asyir who become convicts of terrorism. This puts Ngruki Muslims associated with, even often accused of radicalism and terrorism. Ultimately, it made them uncomfortable with the behavior. The problem is accused of the Ngruki community by other people, making them perceive suffering. It is indicate that they experience victimization. This paper aims to describe the experience of the Ngruki people, who received victimization. The question is, how is the victimization experienced by the Ngruki community?. This study uses the conceptual approach of critical victimology initiated by Sandra Walkalate. This study uses a qualitative method to explore the victimization experiences of from the Ngruki community. by conducting in-depth interviews with five people who experience bad behavior due to their Ngruki identity. This study finds that their identity as Ngruki makes them victims. They get bullying, ribbing, and even discrimination from other people. Nevertheless, there are no resistances, and realize that is normal. Its shows that found "misrecognizeâ€ such as symbolic violence.